(Role of Hydrocolloids in Food Industry)) - Dhiah Nuraini (Balai Besar Industri Agro, 2001)
Food processed industry is increasing growing in a row with development of food technology.In along with the fact, utilization of hydrocolloids is also increasing in order to get good quality processed foods. There are many hydrocolloids that can be applied in food industries. Choosing hydrocolloid which is going to be applied for a product will depend on characteristics of each hydrocolloid, characteristics wanted in the product and other consideration factors.